Mapping of Toronipa Coastal Tourism in Konawe Regency South East Sulawesi Province - Puguh, Lolita Saraswati; Koerniawaty, Francisca Titing; Mahendra, I Wayan Eka (Institut Pariwisata dan Bisnis Internasional, 2022)
This research provides substantial data to reinvigorate Toronipa marine tourism in Konawe Regency, Southeast Sulawesi Province, then this research aims to map the potential attractions around Toronipa beach, and deeply analyze the challenges faced in order to revitalize Toronipa coastal tourism, so that an appropriate development model can be designed for Toronipa coastal tourism destinations. This research implements the initial stage of the Research & Development approach, is a need analysis stage by mapping the potential and challenges with qualitative analysis methods. Data were collected using passive participatory observation techniques, interviews and FGDs. The results showed that the main potential attraction is a beautiful white sandy beach along the 4 km coastline. There are typical Toronipa culinary, tourist facilities in the form of gazebos, toilets, rides and water attractions. The accessibility to destinations is in good condition. The existence of tourism awareness group, tourism human resources and friendly people in welcoming tourists. The challenges faced in developing Toronipa coastal tourism are the unavailability of adequate marine vehicle facilities, the number of artificial attractions is not much, some tourist facilities such as gazebos and toilets are not well maintained, parking lots are still inadequate, and there is no marine tour guide service.